2008
DOI: 10.4161/pri.2.3.7148
|View full text |Cite
|
Sign up to set email alerts
|

Reversible monomer-oligomer transition in human prion protein

Abstract: The structure and the dissociation reaction of oligomers PrP oligo from reduced human prion huPrP C (23-231) have been studied by 1 H-NMR and tryptophan fluorescence spectroscopy at varying pressure, along with circular dichroism and atomic force microscopy. The 1 H-NMR and fluorescence spectral feature of the oligomer is consistent with the notion that the N-terminal residues including all seven Trp residues, are free and mobile, while residues 105~210, comprising the AGAAAAGA motif and S1-Loop-HelixA-Loop-S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…From 15 N studies on ␣-PrP (6, 59), we can conclude that, as in ␣-PrP, these residues are predomi-nantly unstructured (58). This is in contrast to full-length ␤-PrP (residues 23-231), where residues 105-210 appear to be engaged in intra-and/or intermolecular interactions (35). The NMR characteristics of ␤-PrP appear similar to other partially folded molten globule and oligomeric states of PrP (30,32,33), which also contain a predominantly disordered N-terminal region (residues 91-126) and a line broadened, unobservable region corresponding to the folded domain of ␣-PrP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 15 N studies on ␣-PrP (6, 59), we can conclude that, as in ␣-PrP, these residues are predomi-nantly unstructured (58). This is in contrast to full-length ␤-PrP (residues 23-231), where residues 105-210 appear to be engaged in intra-and/or intermolecular interactions (35). The NMR characteristics of ␤-PrP appear similar to other partially folded molten globule and oligomeric states of PrP (30,32,33), which also contain a predominantly disordered N-terminal region (residues 91-126) and a line broadened, unobservable region corresponding to the folded domain of ␣-PrP.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a related study examining the role of the disulfide bond in PrP folding confirmed that a monomeric molten globule-like form of PrP was formed on refolding the disulfide-reduced protein at acidic pH, but reported that, under their conditions, the circular dichroism response interpreted as ␤-sheet structure was associated with protein oligomerization (45). Indeed, atomic force microscopy on oligomeric full-length ␤-PrP (residues 23-231) shows small, round particles, showing that it is capable of formation of oligomers without forming fibrils (35). Notably, however, saltinduced oligomeric ␤-PrP has been shown to be a potent inhibitor of the 26 S proteasome, in a similar manner to PrP Sc (46).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…By observing the pressure response of proteins one obtains not only data on the local and global mechanical and dynamical properties of the macromolecule [4] but can also shift conformational equilibria and stabilize folding and functional intermediates [5][6][7][8]. In addition, physicochemical processes such as pressure induced denaturation, depolymerization, and dissociation can be studied in detail [7,9,10].…”
Section: Introductionmentioning
confidence: 99%